Independent Publisher in the Networks of Translation - Buzelin, Hélène (TTR, 2006)
AbstractOver the past ten years, the publishing and book selling industries (in Canada and elsewhere) have undergone a process of hyper-concentration that seems to threaten the future of independent publishing. How might this changing environment reflect on the attitudes of independent publishers toward translation and on the way they handle translation projects? This is the question this article seeks to examine. It is based on the first case study of a research programme that consists in following, by use of an ethnographic approach, the production process of literary translations in three independent Montréal-based publishing houses: from negotiations over the acquisition of translation rights to the launch of the translation. The article is divided into three parts. The first explains the rationale, methodology and ethics underlying this research; the second part tells the story of the title under study in a way that highlights the range of actors involved in the production of this translation, their own constraints and concerns, as well as the way publishing, editorial and linguistic/stylistic decisions intertwine. Based on this particular case, the third part discusses some of the strategies a publisher and his collaborators may devise in order to produce literary translations in an independent but network-based, competitive way. Particular emphasis is placed on strategies of cooperation such as co-translation and co-edition publishing, as well as on the role played by literary agents in the allocation of translation rights.